Extranjeros, anarquistas y peligrosos : efeitos e possibilidades na imigração a Buenos Aires pelo periódico la protesta humana - Bonacina, Luís Felipe (2023)
During the first half of the XIX century, the vision of the progress, civilization and work that the argentine intellectual elite attributed to the european people was so present that the Nacional Constitucional, of 1853, encouraged immigration to the argentine territory with the ends to attending a capitalistic project of modernization of the country. But in the first years of the XX century, the fear of anarchists demanded that the Argentine State controlled the entry of certain immigrants, at the same time that it implemented the immediate expulsion of those who did not meet the old expectations regarding the values brought from Europe. Therefore, the present dissertation is dedicated to presenting the way in which European immigration to Buenos Aires was represented by the anarchist periodical La Protesta Humana. By the newspaper's doctrinaire nature the research reflects on how the criticism of domination and defense of self-management, two fundamentals concepts of the anarchism, were constructed in the discourses of this militant media in order to co-opt the foreign mass, resident in the Argentine capital, to the libertarian strand of the workers' movement of the city. As such, in addition to a history of immigration to Buenos Aires conceived from the perspective of anarchist workers active during the early years of the newspaper, from 1897 to 1904, the research aims to demonstrate how the theoretical and ideological bases of anarchism were synthesized in the journal to dialogue specifically with the foreign mass of Buenos Aires and transform it into a potentially revolutionary social force